World in crisis : classic accounts of World War II - Lord, Walter, 1917-2002; Craig, William, 1929-; Tregaskis, Richard, 1916-1973 (Open Road Media, 2017)
Three New York Times-bestselling World War II histories, including the true story of the miraculous evacuation portrayed in the Christopher Nolan film Dunkirk. The monumental scope and breathtaking heroism of World War II are brought to vivid life in three riveting accounts that span the conflict's Western Front, Eastern Front, and Pacific Theater. The Miracle of Dunkirk: The definitive account of the evacuation of 338,000 British and French soldiers from the beaches of Dunkirk. Based on interviews with hundreds of survivors and masterfully woven together into a cinematic portrait, The Miracle of Dunkirk captures a pivotal moment when the outcome of World War II hung in the balance. "Stunning ... The difference between the Lord technique and that of any number of academic historians is the originality of his reportage" (The New York Times). Enemy at the Gates: New York Times bestseller and the inspiration for the 2001 film starring Joseph Fiennes and Jude Law. The siege of Stalingrad lasted five months, one week, and three days. Nearly two million men and women died, and Germany's 6th Army was completely destroyed. Considered by many historians to be the turning point of World War II in Europe, the Soviet Army's victory foreshadowed Hitler's downfall and the rise of a communist superpower. Crafted from five years of exhaustive research and interviews with hundreds of survivors, Enemy at the Gates is "probably the best single work on the epic battle of Stalingrad ... An unforgettable and haunting reading experience" (Cornelius Ryan, author of The Longest Day). Guadalcanal Diary: #1 New York Times bestseller and the basis for the 1943 film starring Anthony Quinn and Richard Conte. Volunteer combat correspondent Richard Tregaskis was one of two journalists to witness the invasion of Guadalcanal, the first major Allied offensive against Japanese forces and the first time in history that a combined air, land, and sea assault had ever been attempted. Hailed by the New York Times as "one of the literary events of its time," Guadalcanal Diary is "a superb example of war reporting at its best" (Mark Bowden, author of Black Hawk Down)